Mastering Your Dissertation c y Sue Reeves, Bartek Buczkowski. - Reeves, Sue.; Buczkowski, Bartek (Cham : Springer International Publishing : Imprint: Springer, 2023)
This reader-friendly guide is specifically designed for any student who has ever had a question about theses as part of their university undergraduate degree course in a life- or health science-related subject. It covers the varied types of projects that exist, including experimental work, surveys, meta-analyses, audits and qualitative and quantitative studies - all in one place. Get support at planning, completing and writing of your research based thesis. By using examples and check lists, this book leads you through the entire process encompassing each chapter of the dissertation. Let the question and answer writing style encourage you and boost your confidence when embarking on what is probably your largest piece of work to date, solved in a step by step approach. The experienced authors have run an enormous number of web and face-to-face workshops to support students in life and health sciences and help them write their dissertations. It became clear that research theses are a considerable source of anxiety and that many essential questions need answering - this book is your solution.
Chapter 1: What will this book cover? -- Chapter 2: How can I get organised? -- Chapter 3: How do I choose a project type and title? -- Chapter 4: What is the best way to work with my supervisor? -- Chapter 5: Do I need to complete an ethics form? -- Chapter 6: How do I write an Introduction? -- Chapter 7: How do I write the Methods chapter? -- Chapter 8: How should I present my Results? -- Chapter 9: How do I write the Discussion chapter? -- Chapter 10: How do I write the Conclusion? -- Chapter 11: How do I reference? -- Chapter 12: Does my dissertation need an abstract? -- Chapter 13: What else should I include in my dissertation? -- Chapter 14: How do I prepare and conduct a successful defense? -- Chapter 15: Other frequently asked questions.
Keywords: Biology; Medical sciences; Dissertations, Academic; Penmanship; Research -- Methodology; Biological Sciences; Health Sciences; Thesis and Dissertation; Writing Skills; Research Skills